Pengembangan Aplikasi Penjadwalan Matakuliah Di Prodi Rekayasa Sistem Komputer Universitas Tanjungpura - rahmi hidayati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Lecture scheduling is an activity to determine the lecture time, the lecturer and the lecture room. Lecture scheduling in the study program of Computer Systems Engineering is still done manually resulting often scheduling conflicts that have been made. Genetic algorithm is an optimization method that can be used to solve it. The parameters used in the genetic algorithm for scheduling are the number of chromosomes, the number of genes, the crossover probability value and the mutation probability value. This scheduling application uses lecture data in odd and even semesters consisting of lecturer, subject, room, day, time, time allocation and time slot data. The fitness score is determined based on the number of clashing lecturers, the number of clashing rooms and the number of student clashes. If the number of clashes is zero, the optimal fitness value is one. Based on the research results, the optimal schedule are 10 chromosomes, 60 genes, 0.7 crossover probability and 0.2 mutation probability.